1984
DOI: 10.1111/j.1440-1819.1984.tb00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Suppression Test in Autistic Children

Abstract: A dexamethasone suppression test (DST) was carried out on autistic and other handicapped children to investigate the function of the hypothalamo‐pituitary adrenal axis (HPA‐axis). The subjects were 19 autistic children consisting of 11 relatively well‐developed and eight poorly‐developed children. The control groups were 26 normal volunteers, 19 patients with schizophrenia and 15 children with mental retardation (MR) or minimal brain dysfunction (MBD). The DST procedures followed the Carroll method. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…The response was graded—cortisol and sAA levels were higher when IQ was lower. Previous research has observed that children with autism with an IQ < 60 (termed poorly developed) had higher plasma cortisol levels before and after the dexamethasone suppression test (Hoshino et al 1984). In a later study, four of five poorly developed AUT were non-suppressors and tended to have higher afternoon cortisol values compared to suppressors (Hoshino et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The response was graded—cortisol and sAA levels were higher when IQ was lower. Previous research has observed that children with autism with an IQ < 60 (termed poorly developed) had higher plasma cortisol levels before and after the dexamethasone suppression test (Hoshino et al 1984). In a later study, four of five poorly developed AUT were non-suppressors and tended to have higher afternoon cortisol values compared to suppressors (Hoshino et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Jensen and colleagues (1985), for example, found that 85% of their participants (11 out of 13) did not show the expected cortisol suppression effect after the DST. Similarly, Hoshino and colleagues (1984; 1987) found that relatively few children and adolescents with autistic disorder exhibited cortisol suppression after the DST, with lack of suppression particularly pronounced for those who were lower functioning.…”
Section: Responsiveness Of Cortisol In Asdmentioning
confidence: 93%
“…For example, Hoshino and colleagues (1984) found that none of the lower functioning children and adolescents with autistic disorder demonstrated cortisol suppression; however, suppression rates for the higher functioning individuals with autistic disorder did not differ from other clinical and non-clinical populations. This was confirmed in the authors’ later study (Hoshino et al, 1987), in which they found that just over one-half of the higher functioning children with autistic disorder, and only 20% of the lower functioning children had the expected cortisol suppression response.…”
Section: Issues and Considerations In Cortisol Studies In Asdmentioning
confidence: 95%
See 2 more Smart Citations